LONG LINE SELECTIVITY ON Epinephelus malabaricus (Bloch and Schneider, 1801) ALONG THOOTHUKUDI COAST, SOUTH EAST INDIA. - B. Sundaramoorthy; Sandeep Kumar; N. Neethiselvan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study on long line selectivity on the fishery of Epinephelus malabaricus (Family - Serranidae) was carried out along Thoothukudi coast. Epinephelus malabaricus formed year round commercial fishery with the peak from the month of October to March along Thoothukudi coast. The ‘J’ type hooks with the number ranging from 5 to 7 were found to be used for commercial exploitation of E. malabaricus along Thoothukudi coast. The study revealed that the hook number no 7 might be discouraged as it captured mainly juveniles of E .malabaricus and hook no 5 and 6 were found ideal for the commercial exploitation of E. malabaricus.